High-Frequency Features in the Distribution of Relaxation Times Related to Frequency Dispersion Effects in SOFCs. Issue 1 (5th January 2022) - Fitzek, Katharina; de Haart, Ute; Fang, Qingping; Lehnert, Werner
Abstract : Electrochemical impedance spectroscopy (EIS) is commonly used for the characterization of electrochemical systems, such as solid oxide fuel cells (SOFCs). In recent years, the distribution of relaxation times (DRT) analysis has attracted increasing interest as a tool for investigating electrochemical loss mechanisms in fuel cells due to its ability to resolve electrochemical features that overlap in complex planes. Among the methods used for the deconvolution of the distribution function of relaxation times, DRTtools is commonly used due to its user-friendly graphical user interface. In this study, we investigate the root cause of the expression of additional DRT features in the high-frequency range and link them to characteristic properties of the processes that contribute to the polarization loss of SOFCs. Identification of the root cause leading to the expression of the features is performed by conducting a simulation study with synthetic EIS spectra that are then analyzed using DRTtools. It has been shown that the constant phase element behavior of high-frequency processes in SOFCs is the root cause of the expression of additional peaks in the high-frequency range of the DRT.